2018
DOI: 10.1007/s11032-018-0784-3
|View full text |Cite
|
Sign up to set email alerts
|

Multienvironment genomic variance decomposition analysis of open-pollinated Interior spruce (Picea glauca x engelmannii)

Abstract: The advantages of open-pollinated (OP) family testing over controlled crossing (i.e., structured pedigree) are the potential to screen and rank a large number of parents and offspring with minimal cost and efforts; however, the method produces inflated genetic parameters as the actual sibling relatedness within OP families rarely meets the half-sib relatedness assumption. Here, we demonstrate the unsurpassed utility of OP testing after shifting the analytical mode from pedigree- (ABLUP) to genomic-based (GBLUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 49 publications
(77 reference statements)
5
44
2
Order By: Relevance
“…Generally, pedigree-based PA estimates in conifer species have been reported to be higher or comparable to marker-based models [11,15,16,19,20,23], but there are also some studies reporting marker-based PA estimates to be higher [13,24,36]. Our results for density and Pilodyn follow the general finding in forest trees, whereas for MFA, a low heritability trait, the PA estimation based on GBLUP model is substantially higher (0.16) compared to the ABLUP model (0.04).…”
Section: Comparison Of Pa and Pc From Methods Based On Pedigree And Mmentioning
confidence: 99%
“…Generally, pedigree-based PA estimates in conifer species have been reported to be higher or comparable to marker-based models [11,15,16,19,20,23], but there are also some studies reporting marker-based PA estimates to be higher [13,24,36]. Our results for density and Pilodyn follow the general finding in forest trees, whereas for MFA, a low heritability trait, the PA estimation based on GBLUP model is substantially higher (0.16) compared to the ABLUP model (0.04).…”
Section: Comparison Of Pa and Pc From Methods Based On Pedigree And Mmentioning
confidence: 99%
“…In the past 2 years, a number of additional experimental GS studies have been reported (Cappa et al, 2017 , 2018 ; Duran et al, 2017 ; Lenz et al, 2017 ; Müller et al, 2017 ; Ratcliffe et al, 2017 ; Tan et al, 2017 , 2018 ; Thistlethwaite et al, 2017 ) (Table 1 ; Resende et al, 2017b ; Chen et al, 2018 ; De Moraes et al, 2018 ; El-Dien et al, 2018 ; Kainer et al, 2018 ; Suontama et al, 2018 ). Many of them in species of Eucalyptus for which public high-throughput genotyping platforms of DArT (Sansaloni et al, 2010 ) and SNPs (Silva-Junior et al, 2015 ) have been available.…”
Section: Gs: Advances and Challenges In Forest Treesmentioning
confidence: 99%
“…GS can increase the rate of genetic gain of breeding cycle by increasing ( i ) because the phenotypes of a much larger number of seedlings in the nursery can be predicted with marker data compared to the number of trees that can be tested in conventional field progeny trials. Additionally, the use of realized genomic relationships is associated with increased accuracy in estimating σ A and breeding values (r) (Hayes et al, 2009 ; El-Dien et al, 2018 ). Yet, in forest trees, the potentially greatest impact of GS on the rate of genetic progress will originate from decreasing ( L ).…”
Section: Perspectives Of Genomic Selection In Tree Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of markers in open-pollinated (OP) families is particularly useful as markers can uncover half-sib and full-sib relationships within the OP families ( El-Kassaby et al 2011 ). This will have a significant impact on the precision and accuracy of the estimated genetic parameters as demonstrated by a number of studies ( Bush and Thumma 2013 ; Gamal El-Dien et al 2016 , 2018 ; Müller et al 2017 ; Klápště et al 2017 ; Klápšte et al 2018 ). In traditional methods, all individuals of an OP family are treated as half-sibs.…”
mentioning
confidence: 99%